Visible-Light Photocatalytic CO2-to-CO and H2O-to-H2O2 by g-C3N4/Cu2O-Pd S-Scheme Heterojunctions - Wei, Ling-Wei; Liu, Shou-Heng; Wang, H Paul (ACS applied materials & interfaces, 2023)
Visible-light photocatalytic conversion of CO2-to-fuels for green electricity is sustainably attractive for alleviating carbon emissions. Photocatalytic CO2-to-CO frequently suffered from relatively low yields, mainly due to ineffective charge transfer rates. A new approach for photocatalytic CO2-to-CO enhanced with effective H+ from H2O-to-H2O2 through the water oxidation reaction (WOR) has been studied in the present work. Here, the nano palladium (9 wt %), serving as a cocatalyst, dispersed on the g-C3N4/Cu2O heterojunctions (i.e., g-C3N4/Cu2O-Pd) has been prepared to facilitate charge separation for the two-electron reduction of CO2 to CO. Experimentally, the g-C3N4/Cu2O-Pd heterojunctions have a higher photocatalytic H2O-to-H2O2 yield than the g-C3N4/Cu2O heterojunction by 5.3 times. The photocatalytic WOR provides sufficient electrons (e-) and H+ (2H2O → H2O2 + 2H+) for CO2-to-CO (CO2(aq) + 2H+ + 2e- → CO(g) + H2O(l)). Relatively high photocatalytic yields of H2O2 (34.0 μmol/mg) and CO (14.6 μmol/mg) affected by the heterojunctions can be achieved. Also, the heterojunctions have a high photostability with a photocatalytic generated CO/H2 ratio of 1.75 approximately. This visible-light photocatalytic CO2-to-CO and H2O-to-H2O2 by the new g-C3N4/Cu2O-Pd S-scheme heterojunctions demonstrates the feasibility of the zero carbon emission approach with additional green oxidant (H2O2) generation.Visible-light photocatalytic conversion of CO2-to-fuels for green electricity is sustainably attractive for alleviating carbon emissions. Photocatalytic CO2-to-CO frequently suffered from relatively low yields, mainly due to ineffective charge transfer rates. A new approach for photocatalytic CO2-to-CO enhanced with effective H+ from H2O-to-H2O2 through the water oxidation reaction (WOR) has been studied in the present work. Here, the nano palladium (9 wt %), serving as a cocatalyst, dispersed on the g-C3N4/Cu2O heterojunctions (i.e., g-C3N4/Cu2O-Pd) has been prepared to facilitate charge separation for the two-electron reduction of CO2 to CO. Experimentally, the g-C3N4/Cu2O-Pd heterojunctions have a higher photocatalytic H2O-to-H2O2 yield than the g-C3N4/Cu2O heterojunction by 5.3 times. The photocatalytic WOR provides sufficient electrons (e-) and H+ (2H2O → H2O2 + 2H+) for CO2-to-CO (CO2(aq) + 2H+ + 2e- → CO(g) + H2O(l)). Relatively high photocatalytic yields of H2O2 (34.0 μmol/mg) and CO (14.6 μmol/mg) affected by the heterojunctions can be achieved. Also, the heterojunctions have a high photostability with a photocatalytic generated CO/H2 ratio of 1.75 approximately. This visible-light photocatalytic CO2-to-CO and H2O-to-H2O2 by the new g-C3N4/Cu2O-Pd S-scheme heterojunctions demonstrates the feasibility of the zero carbon emission approach with additional green oxidant (H2O2) generation.